2022
DOI: 10.1109/tasc.2022.3141970
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Runaway of Conduction-Cooled Monofilament and Multifilament Coated Conductors

Abstract: We experimentally studied the thermal runaway initiating at a low critical current (Ic) part. This low Ic part is determined by the combination of two reasons in a real coil: (a) the unavoidable defects caused by the manufacturing process, which reduce local critical currents (and might not be uniform across the width of a coated conductor) and (b) the magnetic field distribution along the coated conductor. To simulate the thermal runaway using a short monofilament/multifilament REBa2Cu3Oy (RE-123) coated cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 32 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Such an approach disregards possible lateral distribution of the defects causing local I c reductions that has been revealed in magnetic mapping, optical scanning and Raman spectroscopy [9][10][11][12][13]. It is also clear that defects in different lateral positions could have different impacts on the Tapestar results and on the tape performance [14][15][16]. Nevertheless, in the experiments observing bubble creation in a nitrogen bath, it was found that the overheated zones appear in strips crossing the full width of the tape, probably because of current congestion around defects [17,18].…”
Section: Methodology Used For Analyzing the Datamentioning
confidence: 99%
“…Such an approach disregards possible lateral distribution of the defects causing local I c reductions that has been revealed in magnetic mapping, optical scanning and Raman spectroscopy [9][10][11][12][13]. It is also clear that defects in different lateral positions could have different impacts on the Tapestar results and on the tape performance [14][15][16]. Nevertheless, in the experiments observing bubble creation in a nitrogen bath, it was found that the overheated zones appear in strips crossing the full width of the tape, probably because of current congestion around defects [17,18].…”
Section: Methodology Used For Analyzing the Datamentioning
confidence: 99%